Statistical Analysis of the Average Per Capita Income of the Population of the Russian Federation ("Journal "U". Economy. Management. Finance.", 2021)
This article analyzes per capita spending, the results of which were revealed growth of this indicator in the period from 2009 – 2019. The author of the article proposed appropriate measures for the introduction of factors that affect the dynamics of the growth of average per capita spending of the population until 2025.
Keywords: monetary income; population; per capita monetary income; model; tables; factor analysis; progression; trends; coefficient